2013
DOI: 10.1515/jpm-2013-0115
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of cervical length as a predictor of preterm delivery: a systematic review

Abstract: We conclude that a short cervix is predictive of preterm delivery and can identify women that may benefit from preventive and therapeutic measures, however, a negative result is not always reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 3 publications
2
23
0
1
Order By: Relevance
“…Sonographic measurement of cervical length (CL) at mid-gestation has been shown to be predictive of PTB in singleton 11, 23-28 and twin gestations 12, 29-39 . This, in turn, has led to the relatively common practice of serial monitoring of CL during the second trimester in women at risk of PTB, including women with twin gestations.…”
Section: Introductionmentioning
confidence: 99%
“…Sonographic measurement of cervical length (CL) at mid-gestation has been shown to be predictive of PTB in singleton 11, 23-28 and twin gestations 12, 29-39 . This, in turn, has led to the relatively common practice of serial monitoring of CL during the second trimester in women at risk of PTB, including women with twin gestations.…”
Section: Introductionmentioning
confidence: 99%
“…4850 Despite providing useful insights concerning diverse populations, designs and analytical methods, prior reviews 912, 17, 44, 4852 failed to consider PCCR with most investigators focusing entirely on CL as measured by TVU. 17, 44, 4951 Reports from five investigative teams 912, 48, 52, 53 over the past 15 years did not cite Papiernik et al’s screening paper from 1986 27 but considered some of the hypotheses which form the basis for the present analysis. The first was Leitich and colleagues from Austria who concluded dilatation of the internal cervical os to be among the most effective markers for preterm delivery.…”
Section: Introductionmentioning
confidence: 93%
“…8 Finally, Barros-Silva and colleagues from Portugal reported inconsistent findings in comparing combined screening targets to short CL alone in three studies, and recommended combining CL “with other markers (sonographic, biochemical and/or clinical) that reflect the multiplicity of mechanisms involved in the pathogenesis of SPTD”. 53(5) …”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of 18 studies, performed by Barros-Silva et al, confirmed that shortening of cervical length in the second trimester is highly predictive of spontaneous preterm delivery. The cut-off range varied from 10 mm to 30 mm, but the value of 25 mm (10th percentile) was used the most frequently [4] . Iams et al found that the relative risk of preterm delivery increased as the length of the cervix decreased.…”
Section: Commentmentioning
confidence: 99%